Development and validation of social inclusion scale for stock market participation - S. M. Riha Parvin; Niyaz Panakaje; Madhura K; Niha Sheikh; Shakira Irfana (Cogent Economics & Finance)
Social inclusion is essential to inclusive development but is less explored in relation to financial behavior, especially stock market participation. This study aims to develop and validate a social inclusion scale specific to stock market participation. The study used literature review, expert insights, and focus groups to identify social inclusion items, followed by Exploratory and Confirmatory Factor Analyses (EFA and CFA) using SPSS and AMOS 23 to check validity. The scale identifies three main dimensions: social interaction, social capital, and peer effect. Social interaction reflects engagement with social groups during major investments, peer effect captures the influence of peers' investment success, and social capital highlights the role of resourceful social networks in investment decisions. This scale is a valuable tool for investors, financial institutions, regulatory bodies, and researchers to assess social inclusion's impact on stock market participation and shape policies for market inclusivity. This study fills a gap by providing a validated scale for social inclusion among stock market participants, offering insights into how social factors influence financial behavior.